2021
DOI: 10.1111/jbi.14222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora

Abstract: Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“… Bayesian phylogeographical reconstruction of ancestral area of the Pedicularis siphonantha complex in the Sino-Himalayan region using the modified nrITS + ptDNA dataset (see above). Pie charts and thickness of branch represent the marginal probabilities for potential ancestral areas with each subregion ( Liu et al, 2021 ), represented by a different color. BI PPs are above branches (* = 1.00).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Bayesian phylogeographical reconstruction of ancestral area of the Pedicularis siphonantha complex in the Sino-Himalayan region using the modified nrITS + ptDNA dataset (see above). Pie charts and thickness of branch represent the marginal probabilities for potential ancestral areas with each subregion ( Liu et al, 2021 ), represented by a different color. BI PPs are above branches (* = 1.00).…”
Section: Resultsmentioning
confidence: 99%
“…The concatenated nrITS and ptDNA dataset, including all samples of the P. siphonantha complex and two outgroups Pedicularis amplituba H. L. Li and Pedicularis tachanensis Bonati, was imported into BEAUti with “beast-classic package” ( Lemey et al, 2009 ). Samples were assigned to one of four subregions of the Sino-Himalayan flora following Liu et al (2021) . Taking into account the center of endemism identified by Zhang et al (2016) , two samples of Pedicularis siphonantha (D1, D2) collected from Yadong country in the middle Himalaya were assigned to subregion IIIa.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have shown that the Qinghai-Tibet Plateau sensu lato (QTPsl) is not a natural tectonic association, but rather comprises a "plateau platform" (i.e., Qinghai-Tibet Plateau sensu stricto; QTPss) [7,8], the Himalaya, and the Hengduan Mountains [9,10]. Together these three regions are also referred to as the pan-Himalayan region [10,11] which boasts of complex topography, diverse geomorphological types, a wide altitudinal range, and different soil textures and geological conditions. This region, where one can observe diverse habitats within a short distance, supports a variety of endemic and endangered species [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Together these three regions are also referred to as the pan-Himalayan region [10,11] which boasts of complex topography, diverse geomorphological types, a wide altitudinal range, and different soil textures and geological conditions. This region, where one can observe diverse habitats within a short distance, supports a variety of endemic and endangered species [11,12]. The pan-Himalayan region is an important biodiversity hotspot with the world's highest diversity of alpine plants, attracting extensive scientific attentions [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation